EDTA (Ethylene Diamine Tetraacetic Acid) AMNa2 coordination substitution derived Fe / M-N-C oxygen reduction electrocatalyst and preparation method thereof
Through the partial coordination substitution reaction between EDTAMNa2 and Fe3+, the preparation process of Fe/Zn-N-C catalyst is simplified, and the problems of cumbersome processes and low active site density in the prior art are solved, and the high activity, stability and Low cost preparation, suitable for a variety of battery applications.
Patent Information
- Application Number
- CN202411775765.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing Fe-N-C catalysts require hard templates and corrosive acids or alkalis during the preparation process, resulting in cumbersome processes, high costs and environmental pollution, and low active site density and yield.
Fe/Zn-N-C electrocatalysts with moderate carbon defects, micropore/grade mesoporous structures, large average pore size, high specific surface area and highly dispersed Fe and Zn species were prepared by partial coordination substitution reaction of EDTAMNa2 and Fe3+. . This method simplifies the preparation process and avoids the use of hard templates and corrosive substances.
It realizes high activity and stability of the catalyst, excellent oxygen reduction reaction performance, including low starting potential, half-wave potential and high kinetic current density, and is cheap, safe and environmentally friendly, suitable for fuel cells and zinc-air batteries .
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oxygen reduction electrocatalysts. Specifically, an EDTAMNa2 (M = Cu, Zn, Co, Fe, Mn) is reacted with Fe 3+ A method for preparing an oxygen reduction electrocatalyst by partial coordination substitution, wherein the catalyst can be used for cathode oxygen reduction reaction in fuel cells and metal-air batteries. Background Art
[0002] The oxygen reduction reaction (ORR) is one of the key reactions in energy conversion devices such as fuel cells and metal-air batteries. Platinum-based catalysts are currently the most widely studied and applied ORR catalysts, but their high price and poor stability limit the large-scale commercialization of technologies such as fuel cells. The development of cheap, efficient and stable ORR catalysts is an important way to reduce the cost of these power generation technologies while improving their energy conversion efficiency, and therefore has important practical significance. A large number of literatures have reported that MNC (M = Fe, Co, Mn, etc.) materials are one of the most promising catalysts to replace platinum for ORR, especially Fe-NC materials.
[0003] The Fe-NC catalysts prepared by direct pyrolysis of carbon-nitrogen precursors and iron sources generally have low specific surface area and nitrogen content, and the iron species produced in the initial stage of the pyrolysis process are easy to migrate and aggregate into metallic Fe, Fe3C, Fe x O y The large-sized crystalline iron species particles greatly reduce the FeN x Density and exposure rate of active sites. Currently, the hard template method is usually used to synthesize atomically dispersed Fe-NC catalysts, which show efficient electrocatalytic performance for ORR. However, this strategy usually requires additional synthesis of templates and subsequent cumbersome processes such as etching the template with corrosive hydrofluoric acid or concentrated alkali, which not only increases the preparation cycle and cost, but also causes environmental pollution and some unsafe factors. In addition, the impregnation loading of nitrogen-containing precursors is limited by the pore volume and specific surface area of the hard template, which will greatly reduce the yield and active site density of the Fe-NC catalyst. Therefore, it is still of great theoretical and practical significance to continue to develop a preparation method for Fe-NC catalysts with a simple process route and high activity and stability, but it also faces huge challenges. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an EDTAMNa2 (M = Cu, Zn, Co, Fe, Mn) 3+Partial coordination substitution produces Fe / Zn-NC electrocatalysts with moderate carbon defects, micropores / hierarchical mesopores, large average pore size, high specific surface area, and highly dispersed Fe and Zn species, preparation methods, and applications. The catalyst exhibits excellent activity and stability in both the three-electrode system cathode ORR and zinc-air batteries, with the characteristics of low-cost raw materials, very simple and controllable process, easy-to-adjust microstructure, high activity and selectivity, and excellent stability.
[0005] The present invention can be implemented by the following technical solutions:
[0006] The invention discloses an Fe / MNC oxygen reduction electrocatalyst derived by EDTAMNa2 coordination substitution, which comprises ethylenediaminetetraacetic acid bimetallic salt EDTAMNa2 and iron halide, wherein the mass ratio of EDTAMNa2 to iron halide is 200:1-0.5:1; in EDTAMNa2, M is one or more of Cu, Zn, Co, Fe and Mn. EDTAMNa2 has carbon, nitrogen, metal precursor and chelating agent, and is obtained by partial substitution reaction with iron halide in liquid phase and then simple thermal cracking and acid leaching.
[0007] Furthermore, the iron halide is one or more of iron fluoride (FeF3), iron chloride (FeCl3) and / or iron bromide (FeBr3).
[0008] Further, the mass ratio of EDTAMNa2 and iron halide is 200:1, 100:1, 60:1, 40:1, 20:1, 4:1, 2:1, 1:1 and / or 0.5:1.
[0009] Another aspect of the present invention is a method for preparing a Fe / MNC oxygen reduction electrocatalyst derived from protected EDTAMNa2 coordination substitution, comprising the following steps:
[0010] S1. Preparation of catalyst precursor: first add EDTAMNa2 to the aqueous solution, stir to dissolve, then add iron halide, continue stirring and then ultrasonically disperse for 0.5-3h, then evaporate, dry and grind the above solution to obtain a catalyst precursor;
[0011] S2. Preparation of primary catalyst: the catalyst precursor obtained in step S1 is reacted under the protection of flowing inert gas under temperature control, and then naturally cooled to room temperature and ground evenly to obtain a primary catalyst;
[0012] S3, acid leaching of catalyst: the primary catalyst obtained in step S2 is leached at 40-80°C and 0.5-2 mol L -1The catalyst is stirred in an acid solution, filtered, washed and dried to obtain a Fe / MNC catalyst from which crystalline metal particles are removed;
[0013] S4. Secondary heat treatment of the catalyst: The Fe / MNC catalyst obtained in step S3 is subjected to temperature control reaction under the protection of flowing inert gas, and then naturally cooled to room temperature to obtain the final Fe / MNC oxygen reduction electrocatalyst derived by EDTAMNa2 coordination substitution.
[0014] Furthermore, in step S2, the heating reaction time is 0.5-3h, and the reaction temperature is 500-900°C.
[0015] Furthermore, in step S2, the flowing inert gas is nitrogen and / or argon.
[0016] Further, in step S3, the acid solution is HCl, H2SO4 and / or HNO3 solution.
[0017] Furthermore, in step S4, the temperature-controlled reaction time is 0.5-3h, and the reaction temperature is 800-1050°C.
[0018] The Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution of the present invention has the following beneficial effects:
[0019] (1) The preparation process of the present invention does not require the use of an additional hard template, because Fe 3+ It has a strong coordination ability with EDTA. The M in EDTAMNa2 2+ Fe in halogenated iron (FeX3, X=F, Cl, Br) 3+ After partial substitution, EDTA has 3+ The multi-dentate directional anchoring and in-situ released double salts (NaX and MX2) will greatly slow down the migration and aggregation of iron species generated during thermal cracking into large-sized crystalline iron particles, while preventing the loss of nitrogen and creating rich micro / mesoscale pore structures. In addition, by simply controlling the substitution reaction of M 2+ / Fe 3+ The molar ratio and M 2+ The type of Fe / MNC can effectively adjust the microstructure of the obtained Fe / MNC material and the electronic structure of Fe active sites, so that it has moderate carbon defects, microporous / hierarchical mesoporous structure, large average pore size, high specific surface area, high active nitrogen species content, highly dispersed Fe / M bimetallic species and suitable spin state characteristics, which is beneficial to increase the density, conversion frequency and utilization rate of active sites in Fe / MNC and promote the transmission of substrates and electrons.
[0020] (2) The Fe / MNC material prepared in the present invention has excellent electrochemical performance: its starting potential, half-wave potential, kinetic current density at high potential, methanol resistance and operational stability for catalytic ORR under alkaline conditions are significantly higher than those of commercial Pt / C catalysts, and its high energy conversion efficiency is 4e - The reaction pathway proceeds; as the cathode catalyst of zinc-air battery devices, the performance of the assembled battery is also better than that of Pt / C.
[0021] (3) In terms of specific applications, the Fe / MNC catalyst of the present invention has a wide range of applications and can be used as a cathode oxygen reduction catalyst for various batteries, such as hydrogen-oxygen fuel cells, direct methanol fuel cells, and zinc-air batteries; in terms of specific raw materials, a small number of types are used and all of them are conventional commercial and inexpensive reagents such as EDTAMNa2 and FeX3 as carbon, nitrogen, metal precursors (also serving as chelating agents) and iron sources, respectively.
[0022] (4) The present invention uses EDTAMNa2 double metal salt to be Fe 3+ The method of preparing Fe / MNC oxygen reduction catalyst by partial coordination substitution requires few raw materials, has low cost, an extremely simple and precisely controllable preparation process, a safe and environmentally friendly process, and is easy for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 SEM photos of EDTAZnNa2-HT2 and xEDTAZnNa2-Fe-HT2 (x=100, 60, 20 and 2).
[0024] Figure 2 TEM photos, HAADF and elemental mapping images of 60EDTAZnNa2-Fe-HT2.
[0025] Figure 3 XRD spectra of EDTAZnNa2-HT2 and xEDTAZnNa2-Fe-HT2 (x=100, 60, 20 and 2).
[0026] Figure 4 Raman spectra of EDTAZnNa2-HT2 and xEDTAZnNa2-Fe-HT2 (x=100, 60, 20 and 2).
[0027] Figure 5 This is the full XPS spectrum of EDTAZnNa2-HT2 and xEDTAZnNa2-Fe-HT2 (x=100, 60, 20 and 2).
[0028] Figure 6N2 adsorption / desorption isotherms and pore size distribution of EDTAZnNa2-HT2 and xEDTAZnNa2-Fe-HT2 (x = 100, 60, 20 and 2).
[0029] Figure 7 VSM curves of EDTAZnNa2-HT2 and xEDTAZnNa2-Fe-HT2 (x=100, 60, 20 and 2).
[0030] Figure 8 Polarization curves of ORR catalyzed by EDTAZnNa2-HT2, xEDTAZnNa2-Fe-HT2 (x = 100, 60, 20 and 2) and Pt / C in O2-saturated 0.1 M KOH (room temperature, scan rate 10 mV s -1 , speed 1600rpm).
[0031] Fig. 9 Polarization curves of ORR catalyzed by 60EDTAZnNa2-Fe-HT2 at different rotation speeds and the number of electrons transferred per O2 molecule at different potentials.
[0032] Fig.10 Methanol resistance of 60EDTAZnNa2-Fe-HT2 and Pt / C at 0.57V.
[0033] Fig.11 Methanol resistance of 60EDTAZnNa2-Fe-HT2 and Pt / C at 0.85V.
[0034] Fig.12 It curve of ORR catalyzed by 60EDTAZnNa2-Fe-HT2.
[0035] Fig.13 Operational stability of 60EDTAZnNa2-Fe-HT2 catalyzed ORR (accelerated stability test).
[0036] Fig.14 is the open circuit voltage of zinc-air batteries assembled with 60EDTAZnNa2-Fe-HT2 and Pt / C as cathode catalysts, respectively.
[0037] Fig.15 The power density curves of zinc-air batteries assembled with 60EDTAZnNa2-Fe-HT2 and Pt / C as cathode catalysts, respectively.
[0038] Fig.16 Specific capacity of zinc-air batteries assembled with 60EDTAZnNa2-Fe-HT2 and Pt / C as cathode catalysts, respectively.
[0039] Fig.17 The rate stability of zinc-air batteries assembled with 60EDTAZnNa2-Fe-HT2 and Pt / C as cathode catalysts, respectively.
[0040] Fig.18 These are the constant current charge / discharge curves of zinc-air batteries assembled with 60EDTAZnNa2-Fe-HT2 and Pt / C as cathode catalysts, respectively. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0042] The invention discloses an Fe / MNC oxygen reduction electrocatalyst derived by EDTAMNa2 coordination substitution, which comprises ethylenediaminetetraacetic acid bimetallic salt EDTAMNa2 and iron halide, wherein the mass ratio of EDTAMNa2 to iron halide is 200:1-0.5:1; in EDTAMNa2, M is one or more of Cu, Zn, Co, Fe and Mn. EDTAMNa2 has carbon, nitrogen, metal precursor and chelating agent, and is obtained by partial substitution reaction with iron halide in liquid phase and then simple thermal cracking and acid leaching.
[0043] Furthermore, the iron halide is one or more of iron fluoride (FeF3), iron chloride (FeCl3) and / or iron bromide (FeBr3).
[0044] Further, the mass ratio of EDTAMNa2 and iron halide is 200:1, 100:1, 60:1, 40:1, 20:1, 4:1, 2:1, 1:1 and / or 0.5:1.
[0045] Another aspect of the present invention is a method for preparing a Fe / MNC oxygen reduction electrocatalyst derived from protected EDTAMNa2 coordination substitution, comprising the following steps:
[0046] S1. Preparation of catalyst precursor: first add EDTAMNa2 to the aqueous solution, stir to dissolve, then add iron halide, continue stirring and then ultrasonically disperse for 0.5-3h, then evaporate, dry and grind the above solution to obtain a catalyst precursor;
[0047] S2. Preparation of primary catalyst: the catalyst precursor obtained in step S1 is reacted under the protection of flowing inert gas under temperature control, and then naturally cooled to room temperature and ground evenly to obtain a primary catalyst;
[0048] S3, acid leaching of catalyst: the primary catalyst obtained in step S2 is leached at 40-80°C and 0.5-2 mol L -1 The catalyst is stirred in an acid solution, filtered, washed and dried to obtain a Fe / MNC catalyst from which crystalline metal particles are removed;
[0049] S4. Secondary heat treatment of the catalyst: The Fe / MNC catalyst obtained in step S3 is subjected to temperature control reaction under the protection of flowing inert gas, and then naturally cooled to room temperature to obtain the final Fe / MNC oxygen reduction electrocatalyst derived by EDTAMNa2 coordination substitution.
[0050] Furthermore, in step S2, the heating reaction time is 0.5-3h, and the reaction temperature is 500-900°C.
[0051] Furthermore, in step S2, the flowing inert gas is nitrogen and / or argon.
[0052] Further, in step S3, the acid solution is HCl, H2SO4 and / or HNO3 solution.
[0053] Furthermore, in step S4, the temperature-controlled reaction time is 0.5-3h, and the reaction temperature is 800-1050°C.
[0054] Example 1
[0055] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The oxygen reduction electrocatalyst prepared by partial coordination substitution, the preparation method thereof comprises the following steps:
[0056] 1) First, add 4.0g EDTAZnNa2 into the aqueous solution, stir for 0.5h, continue ultrasonic dispersion for 2h, and then transfer the mixed solution into a petri dish for evaporation, drying, grinding and standby use;
[0057] 2) The solid powder was placed in a quartz boat and placed in a tube furnace at 200 mL min -1 Under N2 protection, at 5℃min -1 The temperature was raised to 700 °C and kept for 2 h, then naturally cooled to room temperature, and then ground evenly for use. The sample at this stage was named EDTAZnNa2-Fe-HT1;
[0058] 3) EDTAZnNa2-Fe-HT1 was heated at 80℃ and 30mL 0.5mol L -1 The sample was stirred in H2SO4 solution, filtered, washed, dried and ground for later use. The sample at this stage was named EDTAZnNa2-Fe-AL.
[0059] 4) Place EDTAZnNa2-Fe-AL in a corundum boat and stir at 200 mL min -1 Under the protection of N2, the temperature was raised to 900℃ at 10℃ / min and maintained for 2h, and then naturally cooled to room temperature to obtain the final oxygen reduction electrocatalyst derived from EDTAZnNa2. The sample at this stage was named EDTAZnNa2-HT2.
[0060] The SEM photos, TEM photos, XRD spectra, Raman spectra, XPS spectra, N2 adsorption and desorption isotherms and pore size distribution, VSM curves and texture parameters of EDTAZnNa2-HT2 synthesized in this example are shown in Figures 1 and 2. Figure 1 , 2 , 3, 4, 5, 6, 7 and Table 1.
[0061] Example 2
[0062] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The oxygen reduction electrocatalyst prepared by partial coordination substitution, the preparation method thereof comprises the following steps:
[0063] 1) First, add 4.0g EDTAZnNa2 and 0.0229g FeCl3·6H2O into the aqueous solution, stir for 0.5h, continue ultrasonic dispersion for 2h, and then transfer the mixed solution into a petri dish for evaporation, drying, grinding and standby use;
[0064] 2) The solid powder was placed in a quartz boat and placed in a tube furnace at 200 mL min -1 Under N2 protection, at 5℃min -1 The temperature was raised to 700 °C and kept for 2 h, then naturally cooled to room temperature, and then ground evenly for use. The sample at this stage was named 100EDTAZnNa2-Fe-HT1, where 100 is the molar ratio of EDTAZnNa2 to FeCl3·6H2O;
[0065] 3) 100 mL of 0.5 mol L EDTAZnNa2-Fe-HT1 was added at 80 °C. -1 The sample was stirred in H2SO4 solution, filtered, washed, dried and ground for later use. The sample at this stage was named 100EDTAZnNa2-Fe-AL.
[0066] 4) Place 100 EDTAZnNa2-Fe-AL in a corundum boat and stir at 200 mL min -1Under the protection of N2, the temperature was raised to 900°C at 10°C / min and maintained for 2h, and then naturally cooled to room temperature to obtain the final oxygen reduction electrocatalyst derived from EDTAZnNa2. The sample at this stage was named 100EDTAZnNa2-HT2.
[0067] The SEM photos, TEM photos, XRD spectra, Raman spectra, XPS spectra, N2 adsorption and desorption isotherms and pore size distribution, VSM curves and texture parameters of 100EDTAZnNa2-Fe-HT2 synthesized in this example are shown in Figures 1 and 2. Figure 1 , 2 , 3, 4, 5, 6, 7 and Table 1.
[0068] Example 3
[0069] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The steps of the preparation method of the oxygen reduction electrocatalyst prepared by partial coordination substitution are the same as those in Example 2, except that the mass of FeCl3·6H2O added in step 1) is changed to 0.0382 g, and the sample finally obtained is named 60EDTAZnNa2-Fe-HT2.
[0070] The SEM photos, TEM photos, XRD spectra, Raman spectra, XPS spectra, N2 adsorption and desorption isotherms and pore size distribution, VSM curves and texture parameters of 60EDTAZnNa2-Fe-HT2 synthesized in this example are shown in Figures 1 and 2. Figure 1 , 2 , 3, 4, 5, 6, 7 and Table 1.
[0071] Example 4
[0072] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The steps of the preparation method of the oxygen reduction electrocatalyst prepared by partial coordination substitution are the same as those in Example 2, except that the mass of FeCl3·6H2O added in step 1) is changed to 0.05725 g, and the sample finally obtained is named 40EDTAZnNa2-Fe-HT2.
[0073] Example 5
[0074] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The steps of the preparation method of the oxygen reduction electrocatalyst prepared by partial coordination substitution are the same as those in Example 2, except that the mass of FeCl3·6H2O added in step 1) is changed to 0.1145 g, and the sample finally obtained is named 20EDTAZnNa2-Fe-HT2.
[0075] The SEM photos, TEM photos, XRD spectra, Raman spectra, XPS spectra, N2 adsorption and desorption isotherms and pore size distribution, VSM curves and texture parameters of 20EDTAZnNa2-Fe-HT2 synthesized in this example are shown in Figures 1 and 2. Figure 1 , 2 , 3, 4, 5, 6, 7 and Table 1.
[0076] Example 6
[0077] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The steps of the preparation method of the oxygen reduction electrocatalyst prepared by partial coordination substitution are the same as those in Example 2, except that the mass of FeCl3·6H2O added in step 1) is changed to 0.5725 g, and the sample finally obtained is named 4EDTAZnNa2-Fe-HT2.
[0078] Example 7
[0079] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The steps of the preparation method of the oxygen reduction electrocatalyst prepared by partial coordination substitution are the same as those in Example 2, except that the mass of FeCl3·6H2O added in step 1) is changed to 1.14495 g, and the sample finally obtained is named 2EDTAZnNa2-Fe-HT2.
[0080] The SEM photos, TEM photos, XRD spectra, Raman spectra, XPS spectra, N2 adsorption and desorption isotherms and pore size distribution, VSM curves and texture parameters of 2EDTAZnNa2-Fe-HT2 synthesized in this example are shown in Figures 1 and 2. Figure 1 , 2 , 3, 4, 5, 6, 7 and Table 1.
[0081] Example 8
[0082] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The oxygen reduction electrocatalyst prepared by partial coordination substitution has the same preparation steps as those in Example 3, except that the 4.0 g EDTAZnNa2 added in step 1) is changed to 3.3737 g EDTACuNa2, and the final sample obtained is named 60EDTACuNa2-Fe-HT2.
[0083] Example 9
[0084] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+The steps of the preparation method of the oxygen reduction electrocatalyst prepared by partial coordination substitution are the same as those in Example 3, except that the 4.0 g EDTAZnNa2 added in step 1) is changed to 3.4873 g EDTACoNa2·H2O, and the finally obtained sample is named 60EDTACoNa2-Fe-HT2.
[0085] Example 10
[0086] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The oxygen reduction electrocatalyst prepared by partial coordination substitution has the same preparation steps as Example 3, except that the 4.0 g EDTAZnNa2 added in step 1) is changed to 3.3004 g EDTAMnNa2, and the final sample obtained is named 60EDTAMnNa2-Fe-HT2.
[0087] Embodiment 11
[0088] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The oxygen reduction electrocatalyst prepared by partial coordination substitution has the same preparation steps as those in Example 3, except that the 0.0229 g FeCl3·6H2O added in step 1) is changed to 0.0096 g FeF3, and the final sample is named 60EDTAZnNa2-Fe F -HT2.
[0089] Example 12
[0090] This embodiment discloses a method of treating EDTAMNa2 with Fe 3+ The oxygen reduction electrocatalyst prepared by partial coordination substitution has the same preparation steps as those in Example 3, except that the 0.0229 g FeCl3·6H2O added in step 1) is changed to 0.0250 g FeBr3. The final sample is named 60EDTAZnNa2-Fe Br -HT2.
[0091] In order to verify the technical effect of the present invention, the above embodiment is tested for performance in the following manner:
[0092] Preparation of working electrode of three-electrode system and ORR performance test
[0093] 3 mg of Fe / Zn-NC oxygen reduction catalyst prepared in Examples 1-3, 5, and 7 was weighed and dispersed into a mixed solution of 0.5 mL of 5 wt% Nafion and deionized water (1 / 9, V / V), and ultrasonically dispersed for 0.5 h. Then 15 uL of the above uniformly dispersed catalyst suspension was transferred to the polished glassy carbon electrode surface (catalyst loading: 459 ug cm -2), baked under an infrared lamp, and used as the working electrode after the solvent was completely evaporated and dried. Then, platinum wire and Ag / AgCl were used as the counter electrode and reference electrode, respectively. Then, the performance of the material in catalyzing ORR in 0.1 M KOH was evaluated in this three-electrode system by electrochemical methods such as cyclic voltammetry (CV), linear sweep voltammetry (LSV), chronoamperometry and accelerated stability test.
[0094] Zinc-air battery performance test
[0095] The specific assembly method of the zinc-air battery is as follows: a 3.2*3.5 cm zinc sheet is polished with coarse to fine sandpaper to remove surface oxides, then ultrasonically washed with anhydrous ethanol for 10 min and dried to serve as the anode; an aqueous solution of 6 M KOH and 0.2 M (CH3COO)2Zn·2H2O is used as the electrolyte; 3 mg of Fe / Zn-NC sample is weighed and dispersed in 450 μL of anhydrous ethanol and 50 μL of nafion (5% wt%) solution, placed in a 5 mL centrifuge tube for ultrasonic dispersion for 30 min or more, and then the catalyst suspension is pipetted with a pipette to coat the gas diffusion layer with a hydrophobic carbon cloth substrate (2×2 cm) until all coating is completed, and then dried under infrared light to prepare an air cathode (catalyst loading of 1.33 mg cm -2 ). The above three parts of anode, electrolyte and air cathode were assembled into a zinc-air battery (ZAB) with a sandwich structure using a customized battery mold, and then tested under a blue battery test system (CT300A) to evaluate the performance of ZAB.
[0096] The polarization curves and activity parameters of the electrocatalytic ORR of EDTAZnNa2-HT2, 100EDTAZnNa2-Fe-HT2, 60EDTAZnNa2-Fe-HT2, 20EDTAZnNa2-Fe-HT2 and 2EDTAZnNa2-Fe-HT2 synthesized in Examples 1-3, 5 and 7 in 0.1 M KOH at 1600 rpm are as follows: Figure 8 As shown in Table 3, the polarization curves of 60EDTAZnNa2-Fe-HT2 catalyzing ORR at different rotation speeds and the number of electrons transferred by each O2 molecule at different potentials are shown in Fig. 9 shown.
[0097] Example 3 The methanol resistance of the synthesized 60EDTAZnNa2-Fe-HT2 and commercial Pt / C at 0.57V and 0.85V vs. RHE is shown in Figure 3. Fig.10 , Fig.11The specific test method is as follows: the electrode potential is kept constant at 0.57V and 0.85V vs. RHE, respectively. At an electrode speed of 1600rpm, the test is first conducted in N2-saturated 0.1M KOH for 5 minutes, and then switched to O2 for continued testing. After a period of time, when the current density has completely stabilized, a certain amount of methanol is quickly added, and the test is continued for a period of time until the current density no longer changes.
[0098] Example 3 The stability of the synthesized 60EDTAZnNa2-Fe-HT2 and commercial Pt / C was determined by chronoamperometry. Fig.12 The specific method of the chronoamperometry test is as follows: the electrode potential is kept constant at 0.85 V vs. RHE, and the electrode rotation speed is 900 rpm, and the test is continuously performed in O2-saturated 0.1 M KOH for 18,000 s.
[0099] The accelerated stability test results of 60EDTAZnNa2-Fe-HT2 synthesized in Example 3 are as follows Fig.13 The specific method of the accelerated stability test is as follows: in an oxygen-saturated 0.1 M KOH solution, after measuring the polarization curve of the sample at 1600 rpm, the potential range of 0.6 to 1.05 V vs. RHE is maintained at a scan rate of 50 mV s -1 After 10,000 cycles of cyclic voltammetry, the polarization curve was tested again at 1,600 rpm and other identical conditions, and the half-wave potentials obtained from the two polarization curves before and after the cycle were compared.
[0100] Example 3 The open circuit voltage, power density, specific capacity, rate performance and cycle stability of the zinc-air battery assembled with the synthesized 60EDTAZnNa2-Fe-HT2 and commercial Pt / C as cathode catalyst were tested as follows Figure 14-18 shown.
[0101] In the examples of the present invention, the commercial Pt / C (20 wt. % Pt) used for comparison is produced by Johnson Matthey Co. Unless otherwise specified, the characterization and electrochemical testing methods used in the examples are conventional technical methods in the art.
[0102] Table 1 Texture parameters of xEDTAZnNa2-Fe-HT2
[0103]
[0104] Table 2 Relative atomic molar ratio of each element in xEDTAZnNa2-Fe-HT2
[0105]
[0106] Table 3 Activity parameters of xEDTAZnNa2-Fe-HT2 for ORR catalysis in 0.1 M KOH
[0107]
[0108] Combining Tables 1, 2 and 3, it can be seen that, in general, the 60EDTAZnNa2-Fe-HT2 prepared in Example 3 has a large specific surface area (609.26 m 2 g -1 ) and the largest pore volume (0.83 cm 3 g -1 ), average pore size (12.4 nm), and N and Fe content; its onset potential for ORR catalysis (E oneset ), half-wave potential (E 1 / 2 ), limiting current density (J L ) and kinetic current density (J k ) is the highest, even higher than that of the commercial Pt / C catalyst (JM, 20 wt % Pt), where J at high potentials (0.85 and 0.87 V) k They are 2.44 and 1.97 times that of Pt / C respectively.
[0109] Figure 1 The SEM photos of Examples 1-3, 5, and 7 show that the catalyst series exhibit an irregular block morphology with a porous structure, which is mainly attributed to the etching reaction between water, carbon dioxide and other gases released by EDTAZnNa2 during the thermal degradation process and carbon and the evaporation of most zinc ions. Figure 2 The TEM images of Example 3, as well as the high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) and element mapping images, show that the catalyst has an irregular graphitized structure and a rich pore structure; the HAADF-STEM images of randomly selected areas and the energy dispersive x-ray spectroscopy (EDS) element mapping data confirm the hierarchical porous structure of this catalyst and the uniform distribution of C, O, N, Zn and Fe elements. In particular, the Fe and Zn elements are highly dispersed and uniformly distributed in the N element, which will increase the coordination opportunities between them and the N species, thereby forming more atomically dispersed FeN x and ZnN x active sites, thereby improving the activity of catalytic ORR.
[0110] like Figure 3 As shown in the XRD spectra of all samples, two broad diffraction peaks appear near 2θ=21.5° and 43.2°, which are respectively attributed to the (002) and (101) crystal planes of amorphous graphite carbon. 3+ With Zn 2+When the initial molar ratio increases to 1 / 20 and 1 / 2, very weak diffraction peak signals belonging to Fe3O4 appear on the spectrograms of Examples 5 and 7 prepared. Figure 4 For the Raman spectrograms of Examples 1 - 3, 5, 7, Zn in EDTAZnNa2 2+ is coordinated and substituted by Fe with different molar ratios 3+ has no obvious influence on the I of the prepared xEDTAZnNa2 - Fe - HT2 D / I G value, and the calculated I D / I G ≈0.9. Figure 5 For the XPS full spectra of Examples 1 - 3, 5, 7, clear C1s, N1s and O1s peak signals can be observed. Combining with Table 3, it can be seen that as the addition amount of Fe 3+ increases, the atomic percentage of Zn element gradually decreases, indicating that more Zn 2+ is replaced by Fe 3+ ; when the molar ratio of Zn 2+ to Fe 3+ drops to 60, 60EDTAZnNa2 - Fe - HT2 prepared in Example 3 has the highest N and Fe contents.
[0111] Figure 6 For the N2 adsorption / desorption isotherms and pore size distributions of Examples 1 - 3, 5, 7, all show the mixed characteristics of type I / IV isotherms and are accompanied by obvious H3 - type hysteresis loops in the medium - to - high relative pressure range (0.46 < P / P0 < 1.0), indicating the co - existence of micropores and mesopores in the samples prepared in each example. From the specific structure parameters in Table 1 (calculated from the desorption branch), it can be seen that EDTAZnNa2 - HT2 prepared in Example 1 (without iron element) has the smallest average pore diameter (8.7 nm) and the largest specific surface area (770 m 2 g -1 ), and it is worth noting that once iron ions are partially introduced into EDTAZnNa2, even when the molar ratio of Fe 3+ to Zn 2+ is as low as 1 / 100, the specific surface area of 100EDTAZn2Na - Fe - HT2 finally obtained in Example 2 (646 m 2 g -1 ) also decreases significantly; when the molar ratio of Fe 3+ to Zn 2+ continues to increase to 1 / 2, the specific surface area of 2EDTAZn2Na - Fe - HT2 finally obtained in Example 7 starts to decrease significantly again (from 605 to 487 m 2 g -1 ), which may be due to Zn 2+The reduction in the amount of Zn 2 + The effect of evaporative pore formation is reduced.
[0112] like Figure 7 As shown, the saturation magnetization intensity (σ s )With Fe 3+ With Zn 2+ This indicates that more Zn in EDTAZnNa2 2+ Fe 3+ substituted, thereby forming more crystalline iron species during the thermal cracking process. s The highest value is 4.82emu g -1 , while the σ of xEDTAZnNa2-Fe-HT2 (x=100, 60 and 20) prepared in the other three examples s The values are very low (<0.4emu g -1 ), indicating that the content of crystalline iron species in the sample is extremely low. This result is consistent with the XRD analysis results, further confirming that the 2+ / Fe 3+ The molar ratio can be used to control the degree of coordination substitution reaction, which can effectively adjust the relative content of crystalline iron species, thereby reducing the migration and aggregation of iron species into crystalline iron particles and promoting the formation of uniformly dispersed FeN x Achieve a balance between.
[0113] The above results reveal that the ethylenediaminetetraacetic acid bimetallic salt (EDTAMNa2, M = Cu, Zn, Co, Fe, Mn) containing carbon, nitrogen, metal precursor and chelating agent and iron precursor can be used to synthesize Fe in aqueous solution by simply controlling the Fe 3+ Partial coordination substitution of Zn 2+ After thermal cracking and acid treatment, Fe / MNC catalysts with specific structures can be constructed, such as a high degree of graphitization, rich micro / hierarchical mesoporous structure, large specific surface area, highly dispersed zinc / iron species and extremely low content of crystalline iron species. These characteristics are beneficial to promoting ORR and modulating the selectivity of reaction pathways.
[0114] Polarization curves of the oxygen reduction catalysts prepared in Examples 1-3, 5, and 7 and Pt / C catalyzing ORR in O2-saturated 0.1 M KOH and the obtained E onset 、E 1 / 2 , J L and J k Respectively Figure 8As shown in Table 3; the polarization curves of ORR on the Fe / MNC oxygen reduction catalyst prepared in Example 3 at different speeds and the KL equation fitting lines (built-in diagram) at different potentials are shown in Fig. 9 shown.
[0115] The results show that among the Fe / MNC catalysts synthesized in Examples 1-3, 5, and 7, the 60EDTAZnNa2-Fe-HT2 prepared in Example 3 exhibits the highest ORR activity, among which E onset 、E 1 / 2 , J L , J k (0.87V) up to 1.01V, 0.90V, 4.36mA cm -2 and 10.78 mA cm -2 , which are higher than commercial Pt / C. 2+ / Fe 3+ With the decrease of molar ratio, the ORR activity of the five catalysts synthesized in Examples 1-3, 5, and 7 showed a volcano-like change trend, proving that only changing Zn 2+ / Fe 3+ The molar ratio can achieve the purpose of regulating the microstructure of the prepared Fe / MNC catalyst and thus adjusting its ORR activity. Fig. 9 , 10 and 11 are the number of electrons transferred during the ORR catalyzed by 60EDTAZnNa2-Fe-HT2 synthesized in Example 3 and the methanol resistance at relatively low and high potentials, respectively. The results show that the ORR catalyzed by 60EDTAZnNa2-Fe-HT2 is mainly carried out in a 4-electron reaction pathway with high energy conversion efficiency, and has better methanol resistance than Pt / C at both relatively low and high potentials. Fig.12 The chronoamperometry test results showed that at a constant potential of 0.85 V, after 18,000 seconds of testing, the current density of ORR on Pt / C and 60EDTAZnNa2-Fe-HT2 catalysts decreased by 27.3% and 11.6%, respectively, indicating that the latter has higher operational stability. Fig.13 Polarization curves of ORR catalyzed by 60EDTAZnNa2-Fe-HT2 and Pt / C synthesized in 3 before and after 10000 cycles of CV (0.6-1.05V) scanning. E of ORR catalyzed by 60EDTAZnNa2-Fe-HT2 and Pt / C after 10000 cycles 1 / 2 The negative shifts were only 7 mV and a significant 27 mV respectively. This more demanding accelerated stability test result still shows that 60EDTAZnNa2-Fe-HT2 exhibits superior operational stability than Pt / C.
[0116] Due to the excellent ORR performance of 60EDTAZnNa2-Fe-HT2, its practical application in zinc-air battery (ZAB) devices has been further expanded. Fig.14 As shown, ZABs were assembled using zinc foil as the anode and 60EDTAZnNa2-Fe-HT2 prepared in Example 3 and carbon cloth coated with Pt / C catalyst as the cathode, respectively. The ZAB based on the former had an open circuit voltage of 1.49 V, which was slightly higher than the open circuit voltage of the ZAB based on Pt / C (1.47 V). Fig.15 The charge / discharge polarization curves shown in Figure 2 show that the 60EDTAZnNa2-Fe-HT2-based ZAB can output 161.05 mW cm -2 The peak power density is significantly higher than that of Pt / C-based ZAB (122.72 mW cm -2 ).exist Fig.16 Based on the mass normalization of Zn, the 60EDTAZnNa2-Fe-HT2-based ZAB at 20 mA cm -2 The current density was 804.4 mAh g -1 The specific capacity of Pt / C-based ZAB (772.0 mAh g -1 ). At different current densities (1 to 50 mA cm -2 ) were evaluated for the rate performance of 60EDTAZnNa2-Fe-HT2 and Pt / C-based ZABs ( Fig.17 ). Obviously, at the same current density, 60EDTAZn2Na-Fe-HT2-based ZAB can always obtain a higher response voltage than Pt / C-based ZAB. After testing at different current densities for a total of 6 hours, when switching to 5 mA cm -2 At 10 mA cm-1, the response voltage of 60EDTAZn2Na-Fe-HT2-based ZAB recovered to the initial platform value, and the response voltage remained almost unchanged with the test time, indicating its excellent rate performance. -2 Continuous constant current charge / discharge tests were performed under 40 ℃ and 80 ℃ conditions to evaluate the long-term stability of the ZABs they assembled. Fig.18 As shown, the Pt / C-based ZAB could no longer be charged and discharged normally after only 32 hours. In contrast, the 60EDTAZnNa2-Fe-HT2-based ZAB could continue to operate normally for 150 hours, although its voltage efficiency decreased after 57 hours.
[0117] These results reveal that Fe 3+A series of Fe / MNC materials with moderate carbon defects, microporous / hierarchical mesoporous structures, large average pore size, high specific surface area, high content of active nitrogen species and highly dispersed Fe / M bimetallic species were successfully synthesized by coordination substitution reaction with sodium zinc salt of ethylenediaminetetraacetic acid (EDTAZnNa2), thermal cracking, acid leaching and final heat treatment. These characteristics synergistically enable it to exhibit excellent ORR performance and zinc-air battery performance, which are significantly higher than commercial Pt / C catalysts. In addition, the method of synthesizing 60EDTAZnNa2-Fe-HT2 in Example 3 requires less raw materials, low cost, extremely simple and precisely controllable preparation process, safe and environmentally friendly process, and easy large-scale production. Continuing to optimize the preparation conditions such as screening EDTAMNa2 and FeX3 types, controlling their molar ratio, combining two or more EDTAMNa2, doping non-metallic heteroatoms and other simple processes will have great potential to synergize Fe / MNC materials with more excellent ORR performance in hydrogen-oxygen fuel cells and metal-air batteries.
[0118] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. An EDTAMNa2 coordination substitution derived Fe / MNC oxygen reduction electrocatalyst, characterized in that: The EDTAMNa2 coordination substitution derived Fe / MNC oxygen reduction electrocatalyst comprises ethylenediaminetetraacetic acid bimetallic salt EDTAMNa2 and iron halide, wherein the mass ratio of EDTAMNa2 to iron halide is 200:1-0.5:1; in EDTAMNa2, M is one or more of Cu, Zn, Co, Fe and Mn.
2. The Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution according to claim 1, characterized in that: The iron halide is one or more of iron fluoride, iron chloride and / or iron bromide.
3. The Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution according to claim 1, characterized in that: The mass ratio of the EDTAMNa2 to the iron halide is 200:1, 100:1, 60:1, 40:1, 20:1, 4:1, 2:1, 1:1 and / or 0.5:
1.
4. A method for preparing Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution, characterized in that The following steps are involved: S1. Preparation of catalyst precursor: first add EDTAMNa2 to the aqueous solution, stir to dissolve, then add iron halide, continue stirring and then ultrasonically disperse for 0.5-3h, then evaporate, dry and grind the above solution to obtain a catalyst precursor; S2. Preparation of primary catalyst: the catalyst precursor obtained in step S1 is reacted under the protection of flowing inert gas under temperature control, and then naturally cooled to room temperature and ground evenly to obtain a primary catalyst; S3, acid leaching of catalyst: the primary catalyst obtained in step S2 is leached at 40-80°C and 0.5-2 mol L -1 The catalyst is stirred in an acid solution, filtered, washed and dried to obtain a Fe / MNC catalyst from which crystalline metal particles are removed; S4. Secondary heat treatment of the catalyst: The Fe / MNC catalyst obtained in step S3 is subjected to temperature control reaction under the protection of flowing inert gas, and then naturally cooled to room temperature to obtain the final Fe / MNC oxygen reduction electrocatalyst derived by EDTAMNa2 coordination substitution.
5. The method for preparing the Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution according to claim 4, characterized in that: In step S2, the temperature rise reaction time is 0.5-3h, and the reaction temperature is 500-900°C.
6. The method for preparing the Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution according to claim 5, characterized in that: In step S2, the flowing inert gas is nitrogen and / or argon.
7. The method for preparing the Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution according to claim 6, characterized in that: In step S3, the acid solution is HCl, H2SO4 and / or HNO3 solution.
8. The Fe / MNC oxygen reduction electrocatalyst derived from EDTAMNa2 coordination substitution according to claim 7, characterized in that: In step S4, the temperature-controlled reaction time is 0.5-3 hours, and the reaction temperature is 800-1050°C.
Citation Information
Patent Citations
Self-supported Fe-N-C oxygen reduction catalyst and preparation method thereof
CN110137518A